New Insight into Enhanced Photocatalytic Activity of Magnetic MWNTs/TiO2 Nanocomposites - Song, Xiao-Jie; Qin, Zhongqiong; Yang, Fan; Fang, Qun-Ling; Hu, Han-Mei; Zheng, Qiang (Asian Journal of Chemistry, 2015)
Using the carbon nanotubes as carrier and tetrabutyl titanate as precursor, MWNTs/TiO2 nanocomposites are prepared by a sol-gel method,then MWNTs/TiO2/Fe3O4 nanocomposites (magnetic MWNTs/TiO2 nanocomposites) are prepared by a co-precipitation method. The sample is characterized by X-ray powder diffraction, scanning electron microscopy, energy dispersive spectroscopy and transmission electron microscopy. The photocatalytic experiments of MWNTs/TiO2/Fe3O4 nanocomposites are carried out using methyl orange aqueous solution as model pollutant under ultraviolet light. The results indicate that the photocatalytic activity of MWNTs/TiO2/Fe3O4 nanocomposites is the best as the content of MWNTs is about 23 % in MWNTs/TiO2 nanocomposites. The degradation ratio of methyl orange can reach 95 % in 4 h at pH 3. With the help of Fe3O4, MWNTs/TiO2/Fe3O4 nanocomposites can be quickly separated from solution under strong outer magnetic field and used repeatedly.